MANAJEMEN PENGELOLAAN DAN PERENCANAAN KEUANGAN KELUARGA PADA IBU RUMAH TANGGA DI KAWASAN SIWALAN KERTO SURABAYA - Trisnaningsih, Sri; Widyasari, dan Fitria (Journal of Accounting and Strategic Finance, 2010)
This research is conducted with the qualitative method as a mean to collect the circumstantial file, a pregnant data mean the meaning is file which in fact, definitive file representing value at the opposite of visible file. Therefore in research qualitative do not emphasize at the generalizing, but rather emphasize at the meaning. Generalizing in research is qualitative named by transferability, its meaning result of the research can be used in place other;dissimilar, at the moment place own the characteristic which do not far different. While informan weared is a everyday purification housewife always to jump down at family finance. So that information got more circumstantial. The result of research in field, complete and systematic finance record-keeping applying, can assist even give the information which signifikan about estae and properties other information which deal with family finance so that earn more understood by other family member. So that earning better again in taking important decision in family finance. Keywords: Woman Performance, management and finance planning in family